2022
DOI: 10.3390/antiox11122318
|View full text |Cite
|
Sign up to set email alerts
|

Phenolics and Volatile Compounds of Fennel (Foeniculum vulgare) Seeds and Their Sprouts Prevent Oxidative DNA Damage and Ameliorates CCl4-Induced Hepatotoxicity and Oxidative Stress in Rats

Abstract: Researchers recently focused on studying the nutritional and functional qualities of sprouts generated from seeds. The current study investigated the total phenolic content (TPC), total flavonoids (TF), total flavonols (TFL), antioxidant activity (AOA), specific phenolic acids, and volatile chemicals in fennel seeds (FS) and fennel seed sprouts (FSS). The oxidative DNA damage prevention activity of selected FS and FSS extracts against DNA was examined. Consequently, the antioxidative stress potential of FS and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…The essential oil of fennel seeds contains 16.81% trans-anethole (phytosterol) and 47.20% estragol, active substances with antioxidant potential that contribute to the reduction of cholesterol and triglycerides [54]. The total phenolic content of the essential oil extracted from fennel seeds is extremely high and is measured to be 70.42 mg GAE/g [55]. Gharaghani et al [56] showed that consumption of diets containing fennel significantly reduced cholesterol and triglyceride levels in eggs.…”
Section: Discussionmentioning
confidence: 99%
“…The essential oil of fennel seeds contains 16.81% trans-anethole (phytosterol) and 47.20% estragol, active substances with antioxidant potential that contribute to the reduction of cholesterol and triglycerides [54]. The total phenolic content of the essential oil extracted from fennel seeds is extremely high and is measured to be 70.42 mg GAE/g [55]. Gharaghani et al [56] showed that consumption of diets containing fennel significantly reduced cholesterol and triglyceride levels in eggs.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased ALT, AST, and UA in the FS-treated broilers could be explained by the ability of FS administration to maintain liver and renal functions (Ragab, 2007). In addition, several studies reported that FS administration has a hepatoprotective effect against oxidative stress and improves the levels of liver enzymes in rats (Barakat et al, 2022). Due to the hepatoprotective qualities of FS and the fact that a healthy liver controls the metabolism of proteins and amino acids, the higher plasma TP in FS-treated groups may also result from these properties (Charlton, 1996).…”
Section: Advances In Animal Andmentioning
confidence: 95%
“…We found that MDA and CORT levels were linearly decreased as dietary FS levels increased, and this could be linked to the FS's polyphenols and flavonoids in the present study. These components, in turn, have a direct capacity to eliminate free radicals (Barakat et al, 2022). Previous studies have shown that the administration of phenolic compounds from fennel seed significantly lowered MDA levels and returned antioxidant enzyme levels to normal levels in broilers (Ghiasvand et al, 2021) and in rats (Samadi-Noshahr et al, 2021), especially in those animals suffered from stress.…”
Section: Advances In Animal Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Several phytomolecules including soy lecithin, glutamic acid, vitamins, β-carotene, tocopherols and polyphenolics support peripheral nerve regeneration owing to their high antioxidant potential. A very recnt study has evaluated the phenolic composition of FVSE and validated their high antioxidative stress potential [ 19 ]. Recently, it has been observed that crude and methanolic exacts of FV were effective for accelerated recovery after induced PNI [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%